Biocompatibility assessment of glas ionomer cement: Test of cytotoxicity - Marković Dejan (Serbian Medical Society - Dental Section, Belgrade, 2002)
Evaluation o f cytotoxicity is a first step in assessment of dental materials biocompatibility. Necessity for unique criteria in researches resulted in international standard methodology (ISO). The aim of this study was to assess the cytotoxicity of four restorative materials (three glas ionomer cements and one composite material) and to define adventages and disadventages of common ISO methodology for evaluation of this aspect of dental materials biocompatibility. Research was designed according to ISO/TC 106/1995 and ISO/ 10993-5/1994 methodology. Materials used in this investigation were Fuji IILC (GC), Vitiemer (3M), Ionosit fill (DMG-Hamburg), Luxat (DMG-Hamburg). Evaluation of cytotoxicity was carried out on standardized Human Diploid Cell Lung WI-38. Obtained results showed expressive cytotoxic effect of all investigated materials without statisticaly significant difference. Estimation of material biocompatibility and assessment of obtained results can be made only after establishment of correlation with test results. Common ISO methodology is simple for conductance and reproduction, and use of cell cultures in researches is painless, cost effective and without moral or ethical dilemma.